Clinical Impact of Single and Dual Antiplatelet Therapy Beyond 12 Months on Ischemic Risk in Patients With Acute Myocardial Infarction - Roh, Ji Woong; Bae, SungA; Kim, Yongcheol; Son, Nak-Hoon; Cho, Deok-Kyu; Kim, Jung-Sun; Kim, Byeong-Keuk; Choi, Donghoon; Hong, Myeong-Ki; Jeong, Myung Ho; Jang, Yangsoo, the KAMIR-NIH Investigators (Frontiers in Cardiovascular Medicine, 2021)
Background: There is ongoing debate regarding the optimal antiplatelet strategy beyond 12 months in patients with acute myocardial infarction (AMI) who undergo successful percutaneous coronary intervention (PCI). This study therefore aimed to investigate the clinical outcomes of single (SAPT) versus dual antiplatelet therapy (DAPT) beyond 12 months in patients with stable AMI and second-generation drug-eluting stent (DES) implantation. Methods: Of 13,104 patients from the Korea Acute Myocardial Infarction Registry-National Institutes of Health database, we selected 4,604 patients who underwent PCI with second-generation DES and exhibited no adverse clinical events within 12 months; they were classified into SAPT (aspirin or clopidogrel) or DAPT (aspirin and clopidogrel) groups. The primary endpoints were major adverse cardiac and cerebrovascular events (MACCE), including the composite of all-cause death, myocardial infarction (MI), and stroke between 12 and 36 months. Results: The SAPT group (n=1,862) was associated with a significantly lower risk of MACCE between 12 and 36 months (4.2% vs. 8.5%, hazard ratio [HR]: 0.47, 95% confidence interval [CI]: 0.37–0.61; p<0.001) than the DAPT group (n=2,742). The results were consistent after adjusting for confounders through multivariable and propensity score matching analysis. Moreover, in patients with complex features (defined as an unprotected left main PCI, implanted stent length of ≥38 mm, multivessel PCI, or ≥3 stents per patients), the SAPT group (n=678) also demonstrated a significantly lower risk of MACCE between 12 and 36 months (4.9% vs. 9.9%, HR: 0.46, CI: 0.31–0.68, p<0.001) than the DAPT group (n = 1,167). Conclusions: In patients with AMI who underwent successful PCI with second-generation DES and exhibited no adverse clinical events within 12 months, the use of SAPT was associated with a significantly lower MACCE between 12 and 36 months compared with the use of DAPT.